The Effect of Interval Training on 30 Meters Sprint Running Speed ​​in Elementary School Students - Ryan Ali Alfarizi; Tedi Supriyadi; Dinar Dinangsit (Journal Coaching Education Sports, 2026)
This study aimed to examine the impact of interval training on 30-meters sprint speed in elementary school children. This study emphasized the importance of appropriate training methodology to improve students' physical fitness, particularly in speed ability. This study used a quantitative methodology with a quasi-experimental design featuring a pretest-posttest control group. The study sample consisted of 54 sixth-grade students divided into an experimental group and a control group. The experimental group underwent interval training for four weeks, while the control group followed traditional physical education instruction. Data collection was conducted by assessing the 30-meters sprint. Data analysis used descriptive statistics and non-parametric testing, specifically the Wilcoxon and Mann–Whitney tests. The results showed a significant increase in the experimental group from pretest to posttest. However, there was no significant difference between the experimental and control groups in the posttest results. These findings indicate that interval training can improve sprint speed, but has not shown significant benefits compared to traditional techniques. The uniqueness of this study lies in the implementation of interval training in the elementary school physical education curriculum, using a controlled experimental methodology. Although interval training improved sprint performance within the experimental group, it did not produce significantly greater improvements compared to traditional physical education methods